The role and regulation mechanism of Chinese traditional fitness exercises on the bone and cartilage tissue in patients with osteoporosis: A narrative review - Sun, Weibo; Zhang, Xin-An; Wang, Zhuo (Frontiers in Physiology, 2023)
Osteoporosis (ops) is a kind of systemic degenerative bone disease, which is characterized by decreasing bone mass, decreasing bone density, bone microstructure destruction, increasing bone fragility and fracture prone. To date, drug therapy is the main method of the prevention and treatment of osteoporosis. However, long-term drug treatment will inevitably lead to drug resistance and certain side effects. In response, it is generally recommended that it should be given priority to rehabilitation treatment, supplemented by drugs and coordinated with treatment. Chinese traditional fitness operation is an organic combination of sports and traditional Chinese medicine. It has the advantages of being safe, convenient, non-toxic and harmless. It is one of the rehabilitation methods widely used in clinical practice. By searching CNKI, PubMed, Web of science, Embase, Cochrane Library and other relevant databases, our research clarifies the current situation of four kinds of Chinese traditional fitness exercises widely used in clinical practice including Taijiquan, Baduanjin, Wuqinxi, and Yijinjing, and the clinical application in osteoporosis was also summarized in this paper. Based on the research, it was found that Chinese traditional fitness exercise is expected to directly stimulate bone through mechanical load to improve bone density. Furthermore, Chinese traditional fitness exercise may also regulate the endocrine system to mediate the secretion of hormones and factors, as well as indirectly reduce bone loss. The various means of Chinese traditional fitness exercises have different emphasis, and the effect of improving bone density differ in various parts of our bodies. The exercisers may choose flexibly according to their own needs. Chinese traditional fitness exercise is able to improve the bone density of exercisers, as well as relieving pain, improving balance, and regulating psychological state. As a result, it is worth popularizing in clinical practice.